2016
DOI: 10.1051/matecconf/20164705010
|View full text |Cite
|
Sign up to set email alerts
|

PleurotusSpent Mushroom Compost as Green Supplementary Nutrient in Tissue Culture

Abstract: Abstract. This study investigates the effect of Pleurotus spent mushroom compost as green supplementary nutrient in tissue culture. Different concentration of Pleurotus spent mushroom compost in powder (SMC) and activated carbon (SMCAC) were added into Murashige and Skoog media (MS) with 0.1 mg/L 6-benzylaminopurine (BAP). The shoot regeneration of Clinacantus nutans plant such as number of shoots, number of leaves and length of leaves were recorded for four weeks. Collected data was analyzed using one way ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Upon all concentrations of SMC tested on the fig culture, 10% of SMC shows slightly higher proliferation of shoot indicates that small amount of SMC could contribute to new formation of shoots at the cutting area. This is in line with the study conducted by Tay et al, 2016 [16] which SMC as an excellent candidate for supplementary nutrient in tissue culture technique but showed a reverse relationship for number of shoot with increase of SMC concentrations. As for length of shoot and number of leaves, higher concentration show higher performance for production of leaves.…”
Section: Resultssupporting
confidence: 92%
“…Upon all concentrations of SMC tested on the fig culture, 10% of SMC shows slightly higher proliferation of shoot indicates that small amount of SMC could contribute to new formation of shoots at the cutting area. This is in line with the study conducted by Tay et al, 2016 [16] which SMC as an excellent candidate for supplementary nutrient in tissue culture technique but showed a reverse relationship for number of shoot with increase of SMC concentrations. As for length of shoot and number of leaves, higher concentration show higher performance for production of leaves.…”
Section: Resultssupporting
confidence: 92%
“…9 shows that T3c was the most optimum media to be applied for high leaves formation. In [25] have done a slightly similar research on C. nutans by using SMC only in the growth media. The result found that SMC only did give significant high number of leaves at average 7.…”
mentioning
confidence: 99%
“…Consequently, a fast propagation in-vitro tissue culture technique is considered by researchers in order to produce enormous high quality and quantity of plantlets in short time. However, this technique is high in cost due to synthetic hormone and additional chemicals [2]. With this regards, an alternative nutrient source is addressed to enhance shoot propagation and cost reduction.…”
Section: Introductionmentioning
confidence: 99%